The anti-photoaging effect of antioxidant collagen peptides from silver carp (Hypophthalmichthys molitrix) skin is preferable to tea polyphenols and casein peptides. Issue 4 (7th March 2017) - Zhang, Ling; Zheng, Yayao; Cheng, Xiaofeng; Meng, Mengfei; Luo, Yongkang; Li, Bo
Abstract : The anti-photoaging effect of ACPs is preferable to TP and CP, and HCP is better than LCP and MCP. Abstract : Applying antioxidants to attenuate skin photoaging has received great attention. In this study, antioxidant collagen peptides (ACPs) with different activities were prepared using different proteases, called high (HCP), medium (MCP) and low antioxidant collagen peptides (LCP). The effects of ACPs, tea polyphenols (TP) and casein peptides (CP) on the photoaged skin of mice were evaluated and compared. Ingestion of ACPs significantly alleviated UV-induced abnormal alterations of skin components and antioxidative indicators in both serum and skin ( p < 0.05). In addition, HCP had the best effect on protecting skin from photoaging among the three collagen peptides, with no significant differences between MCP and LCP ( p > 0.05). TP and CP, with higher antioxidant activity in vitro, only significantly increased hydroxyproline content (only in the TP group) and CAT activity and decreased protein carbonyl content at week 2, showing a much weaker effect than that of the ACP groups. The histological analysis result further demonstrates that ACPs exerted a stronger beneficial effect on normalizing skin structure and collagen arrangement than TP and CP. Accordingly, ACPs have potential for nutraceuticals as anti-skin-photoaging ingredients.